Establishment of anammox coupled with sulfide-depending autotrophic denitrification process and its efficient pollutants removal performance. (February 2023) - Zhang, Hongli; Zhang, Xiaojing; Wei, Denghui; Wen, Xiaoyu; Zhou, Shijie; Li, Yuqi; Dong, Yongen; Gong, Yaoyao
Abstract: Nitrogen and sulfur pollutants coexist in many industrial wastewaters, which may cause serious water pollution issues. In this study, Anammox coupled with sulfide-depending autotrophic denitrification process (coupling process) was established by adding sulfide to an Anammox system in a membrane bioreactor. Variations in nitrogen and sulfur removal performance, extracellular polymeric substances (EPS), key enzyme activities, and microbial components were analyzed. The sulfide in 25.0 mg L −1 successfully induced denitrification, and then helped establish the coupling process. This process achieved 96.1% TN removal and complete sulfide removal when the sulfide was increased to 100.0 mg L −1 . The protein and polysaccharide in EPS gradually increased to 2.0 and 4.9 mg g −1 SS, respectively. The hydroxylamine oxidoreductase activity, Heme-c content, nitrite reductase activity, and nitrate reductase activity slightly decreased to 19.1 EU g −1 SS, 0.001 mmol g −1 SS, 0.002 μg min −1 mg −1 protein, and 0.005 μg min −1 mg −1 protein, respectively, indicating the slight suppression of sulfide in high concentration on the coupling process. However, after acclimatization, the Anammox and denitrifying bacteria interacted and cooperatively contributed to the simultaneous nitrogen and sulfur removal, with relative abundances of Thiobacillus -denitrifying bacteria and Candidatus Kuenenia -Anammox bacteria of 31.7% and 9.0%, respectively. The establishing strategy was proposed and then verified in another Anammox system, in which the coupling process was also established, with TN removal increasing from 73.4% to 82.5%. Graphical abstract: Image 1 Highlights: Anammox coupled with sulfide-depended autotrophic denitrification process was established. Sulfide in 25.0 mg L −1 was the effective concentration for inducing denitrification. Sulfide was completely removed by the coupling process. The TN removal increased from 65.9% to 96.1% in the coupling system. Thiobacillus and Candidatus Kuenenia were the dominant genera in the coupling process.